Reducing anti-fat bias toward the self and others: a randomized controlled trial - Emily B. Kramer; Evava S. Pietri; Angela D. Bryan (Journal of Eating Disorders, 2024)
Abstract Despite strong evidence linking anti-fat bias directed toward others with markers of self-directed anti-fat bias, there is a dearth of theory-based research examining the cognitive pathways underlying this relationship, and existing bias-reduction intervention efforts have thus far been conducted with exclusive focus on one domain or the other. Cognitive dissonance (CD)-based interventions have been identified as viable for reducing anti-fat bias directed toward the self and others. However, no study has yet examined whether the effects of these domain-specific interventions (e.g., anti-fat bias towards the self) extend to anti-fat bias in the non-targeted domain (e.g., anti-fat bias towards others). The present study aimed to address these gaps in the literature by comparing effects of brief CD-based interventions targeting anti-fat bias directed toward either the self or others on measures of anti-fat bias. Participants (N = 197, female-identifying undergraduates) were randomized to a writing activity prompting cognitive dissonance about either self-directed or other-directed anti-fat bias, or a bias-consistent control condition. Results indicated that participants in the CD intervention conditions showed significantly greater reductions in both explicit self- and other-directed anti-fat biases than those in the control condition, but results did not significantly differ across CD conditions. This supports the potential utility of interventions simultaneously targeting anti-fat bias in both domains and provides insight into the cognitive pathways underlying these related forms of bias.